The Role of Arabic in Promoting Religious Moderation at Darun Nun Islamic Boarding School - Wafira, Naili Zulfa; Pawi, Muzamil R.; Andrian, Mirzahul; Mustofa, Syaiful (Jurnal Al Burhan, 2025)
The potential for radicalism in educational environments poses a serious challenge to instilling values of diversity and tolerance among religious communities. Educational institutions, particularly Islamic boarding schools, play a strategic role in shaping a generation that is not only intellectually capable but also possesses inclusive and moderate character traits. This study aims to analyze the role of Arabic language learning in enhancing religious moderation awareness among students at Darun Nun. Using a qualitative case study approach, data was collected through observation, in-depth interviews, and documentation, and analyzed using Miles and Huberman's techniques. The results of the study indicate that Arabic language learning through the study of classical texts, contextual learning, active dialogue, and participation in social activities significantly contributes to strengthening the values of tolerance, balance, appreciation of diversity, and an inclusive attitude in the lives of students. This study makes an important contribution to understanding Arabic language learning that is not only linguistically and communicatively oriented but also transformative in shaping the character of students who are wise, open-minded, and able to live harmoniously in a diverse society. These findings also open up opportunities for further exploration in various pesantren contexts and other educational institutions focused on character development.